Disclosure appraisal mediating the association between perceived stigma and HIV disclosure to casual sex partners among HIV+ MSM: a path model analysis. Issue 6 (2nd June 2016) - Li, Haochu; Chen, Xinguang; Yu, Bin
ABSTRACT: HIV stigma is widely believed to be related to HIV disclosure. However, there is a dearth of studies examining the mechanisms that link stigma to disclosure. This is a specific study to assess the relationship between perceived stigma and HIV disclosure to casual sex partners based on a social cognitive theory. HIV+ men who have sex with men (MSM) from two US cities ( N  = 297) completed questionnaires administered using audio computer-assisted self-interviewing. Path modeling analysis was used to assess the theory-based structural relationships. Perceived stigma was negatively associated with attitudes, intention and behavior of HIV disclosure to casual sex partners. The association was fully mediated by disclosure appraisal, including disclosure outcome expectations, costs and self-efficacy. Findings of this study add new knowledge regarding HIV stigma and disclosure, and provide timely data supporting more effective behavioral interventions to encourage HIV disclosure among MSM.